VONIS SANKSI PIDANA TAMBAHAN OLEH HAKIM BERUPA PENGEMBALIAN KERUGIAN KEUANGAN NEGARA OLEH TERPIDANA TINDAK PIDANA KORUPSI DI PENGADILAN NEGERI DENPASAR - I Ketut Rai Setiabudhi (University of Udayana, 2014)
Corruption in Indonesia has been so severed and widespread in thecommunity and very alarming, its development continues to increase from year toyear, both in number of cases and the amount of state financial losses and interms of quality. These criminal offenses commit more systematic and scope intoall aspects of life, Starting from lower level of the dominant and state officials orlaw enforcement. Judge in imposing sanctions not only imprisonment and alsofined an additional punishment, including the return of financial loss to the stateby state corruption, as well as some Denpasar District Court and the Court ofCriminal Acts of Corruption (TIPIKOR) Denpasar. Legal basis of corruption inthe judicial process is used by judges Act NO: 31 Jo Act 1999 NO: 20 of 2001 onEradication of Corruption.